(untitled) (INTEGRATION PROCEEDING, 2023)
Hypertension is threat main for health worldwide. Hypertension based on the etiology distinguished Becomes two that is primary and secondary hypertension. Prevalence hypertension in the world 90-95% is primary hypertension. Riskesdas data shows prevalence highest hypertension happens in groups elderly. Treatment common hypertension is known Public is with therapy pharmacological. Besides therapy pharmacological there is also therapy complementary and alternative that has advantages that is easy, cheap and affordable and minimal effect side. Stew leaf regards is one therapy complementary for lower pressure blood because contain compound the flavonoids contain quarcertin. Quarcertin this is what useful as a vasodilator, antiplatelet, and antiproliferative as well as could lower pressure blood. For knowing influence stew leaf regards to decline pressure blood elderly sufferer primary hypertension. Method of this study used quasi experiment with design nonequivalent control group design. The sampling technique used is purposive sampling, which is divided into 13 groups control and 13 groups treatment. The statistical test used is the Mann Whitney test. The result showed score p-value group treatment after given stew leaf regards for 7 days is = 0.000 < 0.05. Boil leaf regards give significant influence to decline pressure blood elderly sufferer primary hypertension.